Analysis of Economic Performance of Manufacturing Companies in Indonesia - Fernando, Nadim; Fachrurrozie, Fachrurrozie (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This research aimed to analyze the influence of Environmental Performance, Profit Margin, and Environmental Disclosure on the Economic Performance partially, and the influence of the Environmental Performance onEconomic Performance through the Environmental Disclosure as an intervening variable.The research sample included the manufacturing companies that listed in Indonesia Stock Exchange in 2012-2014 and joined the PROPER program by the Ministry of the Environment (MOE),which were composed of 39 companies from the total 141 companies.This research used secondary data from the annual reports of each company obtained from the website of the Stock Exchange (www.idx.co.id) and PROPER report by KLH (www.menlh.go.id). Hypothesis testing in this study used path analysis, t test, and Sobel test. The results of this research indicated that the Environmental Performance and Profit Margin partially has significant influence on the Economic Performance, while the Environmental Disclosure does not have a significant influence toward the Economic Performance, and Environmental Performance has no significant influence on the Economic Performance through the Environmental Disclosure as an intervening variable.